Globalization, the Third World state, and poverty-alleviation in the twenty-first century - Logan, Bernard Ikubolajeh (Aldershot, Hants, England ; Burlington, VT : Ashgate, 2002)
Bringing together US and African contributors to write chapters of an international focus, Professor Logan aims to produce the definitive work on globalization. He argues that the dynamics of the unfolding globalized economic, political, socio-cultural and environmental systems result in poverty.
Includes bibliographical references and index.
oif 21/07/16
Loans
Keywords: Poverty; Globalization; Democracy; Developing countries